Efficiency of wind power production and its determinants. (October 2015) - Pieralli, Simone; Ritter, Matthias; Odening, Martin
Abstract: This article examines the efficiency of wind energy production. Using non-convex efficiency analysis, we quantify production losses for 19 wind turbines in four wind parks across Germany. In a second stage regression, we adapt the linear regression results of Kneip, Simar, and Wilson (2015) to explain electricity losses by means of a bias-corrected truncated regression analysis. The results show that electricity losses amount to 27% of the maximal producible electricity. Most of these losses are from changing wind conditions, while 6% are from turbine errors. Highlights: We examine efficiency of wind energy production in 19 wind turbines across Germany. We propose an alternative method to construct power curves for wind turbines. Using non-convex efficiency analysis methods, we quantify production losses. We explain electricity losses via bias-corrected truncated regression. Electricity losses amount to 27% of the maximal producible electricity.